STUDENTS’ LINGUISTIC ATTITUDE TOWARDS LANGUAGE MISTAKES/ERRORS IN LEARNING AND USING A FOREIGN LANGUAGE - Laiveniece, Diāna; Lauze, Linda (Sustainable Multilingualism / Darnioji daugiakalbystė, 2023)
As the intensity of communication increases, the number of language mistakes/errors increases. Nowadays, the acquisition and use of a foreign language often takes place in parallel, and language mistakes/errors are a natural part of this process but this does not mean that they must be tolerated. The study is based on the results of a sociolinguistic survey obtained in 2018 and 2019. 253 students of four Universities and specialties, as well as different study levels from Liepāja, Ventspils and Rīga participated in the survey anonymously. Most of the respondents indicated that Latvian was their mother tongue; for a small number of participants, it was a second language or a foreign language. The surveyed students also differed in the type and number of foreign languages acquired. The present paper is the second part of a wider study (see the results of the first stage of the research by Laiveniece and Lauze, 2020). The aim of this paper is to characterize students’ linguistic attitude towards language errors in learning and using a foreign language: how to evaluate errors, whether errors are generally permissible, what affects them, and how to eliminate them. In the course of the research, an assumption emerged: the more foreign languages are learned, the more tolerant the linguistic attitude is towards mistakes/errors that are made when speaking a foreign language. However, the analysis of the questionnaire findings did not confirm this. Most of the respondents attributed errors to the language learning process. Whether or not errors were made when speaking a foreign language was determined by the situation and purpose of the communication, as well as the level of language acquisition.